A secondary battery and an electric device

CN122991987APending Publication Date: 2026-10-27SUNWODA MOBILITY ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611080370.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-07-20
Publication Date
2026-10-27

AI Technical Summary

Technical Problem

[0003]本申请的目的在于解决现有技术中二次电池的首圈库伦效率较低、倍率性能较差的技术问题,提出了一种具有较高的首圈库伦效率以及优异的倍率性能的二次电池和用电装置

Benefits of technology

本申请提供的二次电池通过控制在垂直于所述正极活性材料层表面的截面上,所述正极活性材料颗粒截面等效为同等面积圆形的等效粒径在一定范围内且圆润度也在一定范围内的正极活性材料颗粒的数量,占截面上所有正极活性材料颗粒数量的比例在一定范围内,能够有效的实现正极活性材料颗粒和二次电池正极活性材料层中的固态电解质颗粒之间的均匀分散以及良好的固-固接触性能,从而能够有效的提升二次电池的首圈库伦效率和倍率性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure FT_1
    Figure FT_1
  • Figure FT_2
    Figure FT_2
  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application discloses a secondary battery and a power utilization device, and belongs to the technical field of batteries. The secondary battery provided by the application can effectively realize uniform dispersion between positive active material particles and solid-state electrolyte particles in the secondary battery and good solid-solid contact performance, so that the first circle coulomb efficiency and the rate performance of the secondary battery can be effectively improved, by controlling the number of positive active material particles with an equivalent particle diameter in a certain range and a certain roundness in a cross section perpendicular to the surface of a positive active material layer, and the proportion of the number of the positive active material particles in all positive active material particles in the cross section being in a certain range.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This application relates to the field of battery technology, and in particular to a secondary battery and an electrical device. Background Technology

[0002] Rechargeable batteries, especially solid-state batteries, are a key upgrade direction for next-generation lithium-ion batteries, boasting advantages such as high energy density and high safety. They are expected to gradually achieve industrialization in the future, with a broad market prospect. Solid-state electrolytes can be broadly classified into three categories based on material type: polymer, oxide, and sulfide. Among them, sulfide solid-state electrolytes have attracted widespread attention due to their high ionic conductivity and good processability. However, severe interfacial side reactions and high solid-solid interface contact resistance between sulfide solid-state electrolytes and high-nickel ternary cathode materials in the positive electrode lead to problems such as low coulombic efficiency and poor rate performance in the first cycle of rechargeable batteries. Effectively suppressing interfacial side reactions and reducing interfacial resistance are crucial for improving the cycle performance and rate performance of solid-state lithium batteries. Summary of the Invention

[0003] The purpose of this application is to solve the technical problems of low first-cycle coulombic efficiency and poor rate performance of existing secondary batteries, and to propose a secondary battery and power supply device with high first-cycle coulombic efficiency and excellent rate performance.

[0004] To achieve the above objectives, a first aspect of this application provides a secondary battery, the secondary battery comprising a positive electrode sheet, the positive electrode sheet comprising a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector, the positive active material layer comprising positive active material particles, characterized in that, in a cross section perpendicular to the surface of the positive active material layer, the positive active material particles satisfy β1 < 8.5%; Wherein β1 represents the proportion of the number of positive electrode active material particles with an equivalent particle size in the range of [1.4~5) μm and a roundness in the range of [0.45~1] on a cross section perpendicular to the surface of the positive electrode active material layer.

[0005] As an embodiment of this application, the positive electrode active material on the cross section satisfies 13% < β < 32%; where β2 represents the proportion of the number of positive electrode active material particles with an equivalent particle size in the range of [0.8~1.4) μm and a roundness in the range of [0.4~1) on the cross section perpendicular to the surface of the positive electrode active material layer, which is equivalent to a circle of equal area.

[0006] As an embodiment of this application, the positive electrode active material on the cross section satisfies 32% < β3 < 62%; where β3 represents the proportion of the number of positive electrode active material particles with an equivalent particle size in the range of [0.2~0.8) μm and a roundness in the range of [0.3~1.5] on the cross section perpendicular to the surface of the positive electrode active material layer to the total number of positive electrode active material particles on the cross section.

[0007] The equivalent particle size D1 of the positive electrode active material particles on the cross section is equivalent to a circle of equal area, which satisfies 1μm≤D1≤2μm; where D1 is the particle size corresponding to the cumulative volume distribution of the positive electrode active material in the cross section of the positive electrode sheet reaching 50% based on the equivalent particle size.

[0008] As an embodiment of this application, the equivalent particle size D2 of the positive electrode active material particles on the cross section is equivalent to a circle of equal area, which satisfies 2μm≤D2≤5μm; wherein, D2 is the particle size corresponding to the cumulative volume distribution of the positive electrode active material in the cross section of the positive electrode sheet reaching 99% based on the equivalent particle size.

[0009] As an embodiment of this application, the positive electrode active material particles comprise the chemical formula Li a Ni b Co c M d Me e Compounds of O2, wherein 0.95≤a≤1.05, b≥0.8, 0.05≤c≤0.15, 0.05≤d≤0.2, 0≤e≤0.05, b+c+d+e=1; M includes at least one of Mn and Al; Me includes at least one of Al, B, Zr, Zn, Sr, V, Ti, Sr, Sb, Y, W, Nb, Mg, and Ta.

[0010] As an embodiment of this application, at least a portion of the surface of the positive electrode active material particles is provided with a coating layer, the coating layer comprising the chemical formula Li α X β Compounds of O3, wherein X includes one or more of Ti, V, Cr, Zr, Nb, Si, Ta, B, La, Sr, W, and C, 0 < α < 4, 0 < β ≤ 2.

[0011] As an embodiment of this application, the mass percentage of the coating layer is 0.1% to 5% based on the mass of the positive electrode active material particles.

[0012] As an embodiment of this application, the positive electrode active material layer further includes a solid electrolyte; the diameter of the solid electrolyte is 0.2 μm to 1.5 μm.

[0013] As an embodiment of this application, the mass percentage of the solid electrolyte is 1% to 50% based on the total mass of the positive electrode active material layer.

[0014] A second aspect of this application provides an electrical device comprising the secondary battery described in this application.

[0015] Compared with the prior art, the beneficial effects of this application are: The secondary battery provided in this application controls the number of positive active material particles with equivalent particle size and roundness within a certain range on a cross-section perpendicular to the surface of the positive active material layer. The proportion of these particles to the total number of positive active material particles on the cross-section is within a certain range. This effectively achieves uniform dispersion and good solid-solid contact performance between the positive active material particles and the solid electrolyte particles in the positive active material layer of the secondary battery, thereby effectively improving the first-cycle coulombic efficiency and rate performance of the secondary battery. Attached Figure Description

[0016] Figure 1 SEM image of the cross-section of the positive electrode sheet prepared in Example 1; Figure 2 This is an equivalent particle image of the SEM image of the cross-section of the positive electrode sheet prepared in Example 1. Detailed Implementation

[0017] To make the objectives, technical solutions, and advantages of the embodiments of this application clearer, the technical solutions in the embodiments of this application will be clearly and completely described below. Obviously, the described embodiments are only some embodiments of this application, not all embodiments. Based on the embodiments in this application, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this application.

[0018] In this application, the technical features described in an open-ended manner include both closed technical solutions consisting of the listed features and open technical solutions that include the listed features.

[0019] In this application, numerical ranges are referred to as continuous unless otherwise specified, and include the minimum and maximum values ​​of the range, as well as every value between the minimum and maximum values. Furthermore, when the range refers to integers, it includes every integer between the minimum and maximum values ​​of the range. Additionally, when multiple ranges are provided to describe a feature or characteristic, the ranges may be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges to which they are incorporated.

[0020] In one embodiment of this application, a secondary battery is provided, the secondary battery including a positive electrode sheet, the positive electrode sheet including a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector, the positive active material layer including positive active material particles, wherein, in a cross section perpendicular to the surface of the positive active material layer, the positive active material particles satisfy β1<8.5%; Wherein β1 represents the proportion of the number of positive electrode active material particles with an equivalent particle size in the range of [1.4~5) μm and a roundness in the range of [0.45~1] on a cross section perpendicular to the surface of the positive electrode active material layer.

[0021] The secondary battery provided in this application achieves uniform dispersion and good solid-solid contact performance between the positive active material particles and the solid electrolyte particles in the positive electrode sheet of the secondary battery by controlling the equivalent particle size and roundness of the positive active material particles on a cross section perpendicular to the surface of the positive active material layer to meet certain conditions. This results in a ratio of the number of positive active material particles to the total number of positive active material particles on the cross section within a certain range. As a result, the first-cycle coulombic efficiency and rate performance of the secondary battery can be effectively improved.

[0022] It should be noted that the test method for the equivalent particle size of the positive electrode active material particles on the cross section being equivalent to a circle of equal area, and the test method for the roundness α of the positive electrode active material particles on the cross section are as follows: The secondary battery is disassembled to obtain the positive electrode sheet, which is then ion polished with aluminum foil as the substrate and AB glue as the bonding method. Then, the cross section is photographed with a scanning electron microscope (SEM) to obtain SEM images at different magnifications. The particles in the SEM images are identified using Avizo software, and the size and roundness information of the particles are quantified and statistically analyzed. Then, the roundness α of the positive electrode active material particles is calculated using a formula. Wherein, the roundness α = 4πS / L 2 , S represents the cross-sectional area of ​​any positive electrode active material particle in the cross-section of the positive electrode sheet, in nm. 2 ; L is the perimeter of any positive electrode active material particle in the cross-section of the positive electrode sheet, in nm.

[0023] Similarly, the equivalent particle size D can also be obtained by identifying and quantifying the particles in the SEM image using Avizo software. Then, by filtering and calculating D and α, the proportion of positive electrode active material particles that satisfy D and α to the total number of positive electrode active material particles on the cross section can be obtained.

[0024] For example, β1 can be any point value between <8.5% or a range value between any two points, such as 2.43% to 8.25%, or 2%, 3%, 4%, 5%, 6%, 7%, 8%, 8.4%, etc.

[0025] As an embodiment of this application, the positive electrode active material particles on the cross section satisfy 13% < β2 < 32%; where β2 represents the proportion of the number of positive electrode active material particles with an equivalent particle size in the range of [0.8~1.4) μm and a roundness in the range of [0.4~1) on the cross section perpendicular to the surface of the positive electrode active material layer, which is equivalent to a circle of equal area.

[0026] For example, β2 can be any point or any range between 13% (excluding 13%) and 32% (excluding 32%), such as 13.1%, 15%, 18%, 20%, 22%, 25%, 28%, 30%, 31.9%, etc.

[0027] As an embodiment of this application, the positive electrode active material on the cross section satisfies 32% < β3 < 62%; where β3 represents the proportion of the number of positive electrode active material particles with an equivalent particle size in the range of [0.2~0.8) μm and a roundness in the range of [0.3~1.5] on the cross section perpendicular to the surface of the positive electrode active material layer to the total number of positive electrode active material particles on the cross section.

[0028] For example, β3 can be any point value between 32% (excluding 32%) and 62% (excluding 62%) or a range value between any two points, such as 32.1%, 35%, 38%, 40%, 42%, 45%, 48%, 50%, 52%, 55%, 58%, 60%, 61.9%, etc.

[0029] This application research found that the density of the solid-solid contact between the positive electrode active material particles and the solid electrolyte particles in the positive electrode active material layer is related to the particle size and roundness of the positive electrode active material particles. This application controls the roundness of the positive electrode active material particles to be different within different ranges of equivalent particle size, and when the ratio of the number of such positive electrode active material particles to the total number of positive electrode active material particles on the cross section is within a certain range, it can facilitate the highly uniform dispersion of the solid electrolyte around the positive electrode active material particles, ensuring the solid-solid contact cross section and sufficient lithium-ion diffusion channels in the secondary battery; thereby effectively improving the first-cycle coulombic efficiency and rate performance of the secondary battery.

[0030] In one embodiment, the equivalent particle size D1 of the positive electrode active material particles on the cross section is equivalent to a circle of equal area, which satisfies 1μm≤D1≤2μm; wherein, D1 is the particle size corresponding to the cumulative volume distribution of the positive electrode active material in the cross section of the positive electrode sheet reaching 50% based on the equivalent particle size.

[0031] For example, D1 can be any point value between 1μm and 2μm or a range value between any two points, such as 1μm, 1.2μm, 1.4μm, 1.6μm, 1.8μm, 2μm, etc.

[0032] It should be noted that the test method for determining the equivalent particle size D1 of the positive electrode active material particles on the cross section as equivalent to a circle of equal area is as follows: the secondary battery is disassembled to obtain the positive electrode sheet, and then the positive electrode sheet is ion polished with aluminum foil as the substrate and AB glue as the bonding method; then the cross section is photographed with a scanning electron microscope (SEM) to obtain SEM images at different magnifications; the particles in the SEM images are identified and the particle size is quantitatively statistically analyzed using Avizo software.

[0033] This study found that when the equivalent particle size D1 of the positive electrode active material particles on the cross-section is equivalent to a circle of equal area and is within the above-mentioned range, the proportion of small-sized particles in the positive electrode active material particles can be effectively controlled. This allows the interfacial contact area between the positive electrode active material and the solid electrolyte to be controlled within a certain range, reducing interfacial side reactions. This, in turn, improves the first-cycle coulombic efficiency and rate performance of the secondary battery.

[0034] As an embodiment of this application, the equivalent particle size D2 of the positive electrode active material particles on the cross section is equivalent to a circle of equal area, which satisfies 2μm≤D2≤5μm; wherein, D2 is the particle size corresponding to the cumulative volume distribution of the positive electrode active material in the cross section of the positive electrode sheet reaching 99% based on the equivalent particle size.

[0035] For example, D2 can be any point value between 2μm and 5μm or a range value between any two points, such as 2μm, 2.2μm, 2.4μm, 2.6μm, 2.8μm, 3μm, 3.2μm, 3.4μm, 3.6μm, 3.8μm, 4μm, 4.2μm, 4.4μm, 4.6μm, 4.8μm, 5μm, etc.

[0036] It should be noted that the test method for determining the equivalent particle size D2 of the positive electrode active material particles on the cross section as equivalent to a circle of equal area is the same as the test process described above for D1.

[0037] This study found that when the equivalent particle size D2 of the positive electrode active material particles on the cross-section is equivalent to a circle of equal area and is within the above-mentioned range, the solid-solid interface contact between the positive electrode active material particles and the solid electrolyte in the positive electrode sheet can be effectively controlled within a certain range, thereby achieving good kinetic performance of the secondary battery; thus effectively improving the first-cycle coulombic efficiency and rate performance of the secondary battery.

[0038] In one embodiment, the positive electrode active material particles on the cross section are single crystals or near-single crystals.

[0039] In one embodiment, the positive electrode active material particles comprise Li a Ni b Co c M d Me e Compounds of O2, wherein 0.95≤a≤1.05, b≥0.8, 0.05≤c≤0.15, 0.05≤d≤0.2, 0≤e≤0.05, b+c+d+e=1; M includes at least one of Mn and Al; Me includes at least one of Al, B, Zr, Zn, Sr, V, Ti, Sr, Sb, Y, W, Nb, Mg, and Ta.

[0040] This study found that the chemical formula of the positive electrode active material particles affects the kinetic performance of the positive electrode active material, and also affects the particle size and roundness of the positive electrode active material particles to a certain extent, as well as the proportion of positive electrode active material particles with specific particle sizes and roundness. When the chemical formula of the positive electrode active material particles is further selected to be of the above type, the first-cycle coulombic efficiency and rate performance of the secondary battery can be better improved.

[0041] In one embodiment, at least a portion of the surface of the positive electrode active material particles is provided with a coating layer, the coating layer comprising the chemical formula Li α X β Compounds of O3, wherein X includes one or more of Ti, V, Cr, Zr, Nb, Si, Ta, B, La, Sr, W, and C, 0 < α < 4, 0 < β ≤ 2.

[0042] This application research found that having a coating layer on at least a portion of the surface of the positive electrode active material particles can effectively improve the diffusion kinetics of lithium ions at the interface, mitigate interfacial side reactions between the positive electrode active material and the solid electrolyte, and the introduction of the coating layer can also affect the roundness of the positive electrode active material particles to some extent. When the introduced coating layer is further selected to include compounds of the above-mentioned chemical formula, the first-cycle coulombic efficiency and rate performance of the secondary battery can be effectively improved.

[0043] For example, the mass percentage of the coating layer can be any point value between 0.1% and 5% or a range between any two points, such as 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, etc.

[0044] It should be noted that the method for testing the mass percentage of the coating layer is as follows: a cross-section of the positive electrode active material particles is prepared using a cross-section polisher (such as the IB-09010CP argon ion cross-section polisher from JEOL Corporation), the cross-section passing through the core of the positive electrode active material particles; then, elemental analysis is performed by EDX or EDS combined with TEM or SEM (such as the X-Max EDS from Oxford Instruments Group combined with the Sigma-02-33 SEM from ZEISS) to obtain the elemental distribution map in the cross-section; based on the elemental distribution of the cross-section, the elemental types and chemical formulas of the coating layer are obtained. More precisely, the mass percentage of the coating layer can be calculated by obtaining the mass percentage of the corresponding elements using ICP (Inductively Coupled Plasma Emission Spectrometer).

[0045] This study found that the thickness of the coating layer affects the migration path of lithium ions at the interface and also affects the structural stability of the positive electrode active material. When the thickness of the coating layer is further selected within the above range, the resulting secondary battery has higher first-cycle coulombic efficiency and better rate performance.

[0046] In one embodiment, the positive electrode active material layer further includes a solid electrolyte; the diameter of the solid electrolyte is 0.2 μm to 1.5 μm.

[0047] For example, the diameter of the solid electrolyte can be any point value between 0.2μm and 1.5μm or a range between any two points, such as 0.2μm, 0.4μm, 0.6μm, 0.8μm, 1μm, 1.2μm, 1.4μm, 1.5μm, etc.

[0048] It should be noted that the method for testing the diameter of the solid electrolyte is as follows: based on EDX or EDS elemental analysis combined with TEM or SEM surface scanning test, the elemental distribution map in the cross section of the solid electrolyte particle is obtained. Based on the elemental distribution in the cross section, multiple (more than 3, such as 8, 10, 12, etc.) diameters with different orientations are obtained, and the average value is recorded as the average particle size of the positive electrode active material.

[0049] This study found that the diameter of the solid electrolyte affects its solid-solid contact with the positive electrode active material particles, as well as its intrinsic ionic / electronic conductivity. When the diameter of the solid electrolyte is further selected within the above range, the resulting secondary battery has a higher first-cycle coulombic efficiency and better rate performance.

[0050] In one embodiment, the mass percentage of the solid electrolyte is 1% to 50% based on the total mass of the positive electrode active material layer.

[0051] For example, based on the total mass of the positive electrode active material layer, the mass percentage of the solid electrolyte can be any point value between 1% and 50% or a range between any two points, such as 1%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, etc.

[0052] It should be noted that the mass percentage of the solid electrolyte, based on the total mass of the positive electrode active material layer, is determined by means of solution absorption spectroscopy of the positive electrode active material layer, such as ICP (Inductive Coupled Plasma Emission Spectrometer) or XAFS (X-ray absorption fine structure spectroscopy).

[0053] This study found that the mass percentage of solid electrolyte in the positive electrode active material layer affects the ionic / electronic conductivity of the positive electrode and its solid-solid contact capability with the positive electrode active material particles. When the mass percentage of solid electrolyte is further selected within the above range, the resulting secondary battery has a higher first-cycle coulombic efficiency and better rate performance.

[0054] In one embodiment, the solid electrolyte comprises a sulfide solid electrolyte.

[0055] In one embodiment, the sulfide solid electrolyte comprises Li 10 GeP2S 12 Li7P3S 11 Li6PS5Cl, Li 5.5 PS 4.5 Cl 1.5 At least one of Li3PS4.

[0056] In one embodiment, the positive electrode active material layer further includes a positive electrode conductive agent and a positive electrode binder.

[0057] This application does not have any special requirements for the positive electrode conductive agent; any positive electrode conductive agent conventionally available in the art can be used. For example, the positive electrode conductive agent may be at least one of phase-grown carbon fiber (VGCF), acetylene black (AB), carbon nanotubes (CNT), and carbon black (superP).

[0058] This application does not have special requirements for the positive electrode conductive agent; any positive electrode binder conventionally available in the art can be used. For example, the positive electrode binder may be at least one of polyvinylidene fluoride, polyvinyl acid, and polytetrafluoroethylene.

[0059] In one embodiment, the secondary battery further includes a negative electrode.

[0060] This application does not have any special requirements for the negative electrode sheet; any negative electrode sheet conventionally available in the art can be used. For example, the negative electrode sheet may be at least one of a lithium sheet, an indium sheet, or a lithium-indium alloy sheet.

[0061] In one embodiment, the method for preparing the secondary battery includes the following steps: (1) Preparation of positive electrode active material: Nickel-cobalt-manganese ternary material precursor, lithium source, M source and Me source are mixed in stoichiometric ratio and sintered once in oxygen environment. Then the first sintering product is mixed with the coating layer precursor and sintered twice in oxygen atmosphere. The second sintering product is then crushed, graded and sieved to obtain positive electrode active material. (2) Preparation of solid electrolyte layer: Take solid electrolyte powder and spread it evenly into the mold. First, pre-press it with a pressure of 200MPa~400MPa for 2min~10min to make a solid electrolyte layer with a thickness of 0.02mm~5mm. Keep the ambient dew point below -40°C during the pressing process (or carry out in an argon glove box). (3) Preparation of secondary battery: The positive electrode active material, solid electrolyte, positive electrode conductive agent and positive electrode binder are mixed and ground to obtain composite positive electrode material. Then the composite positive electrode material is first pressed on one side of the solid electrolyte layer to obtain positive electrode sheet. Then the positive electrode current collector is pressed on the positive electrode sheet. Next, the negative electrode alloy and current collector are second pressed on the other side of the solid electrolyte layer to obtain a full secondary battery.

[0062] In some embodiments, the nickel-cobalt-manganese ternary material precursor includes at least one of nickel-cobalt-manganese hydroxide, nickel-cobalt-manganese carbonate, and nickel-cobalt-manganese nitrate.

[0063] In some embodiments, the lithium source includes one or more of lithium oxide (Li₂O), lithium phosphate (Li₃PO₄), lithium dihydrogen phosphate (LiH₂PO₄), lithium acetate (CH₃COOLi), lithium hydroxide (LiOH), lithium carbonate (Li₂CO₃), and lithium nitrate (LiNO₃). Further, the lithium source is one or more of lithium carbonate, lithium hydroxide, and lithium nitrate; even further, the lithium source is lithium carbonate.

[0064] In some embodiments, the M source and Me source include at least one of oxides, nitrates, carbonates, bicarbonates, sulfates, chlorides, hydroxides, and acetates of the elements M and Me.

[0065] In some embodiments, the coating precursor includes at least one of an oxide, nitrate, carbonate, bicarbonate, sulfate, and hydroxide of element X.

[0066] In some embodiments, the temperature of the first sintering is 600℃~1000℃, for example 600℃~900℃, or even 650℃~850℃, which is beneficial for achieving high doping uniformity of M and Me elements. The sintering time can be adjusted according to actual conditions, for example 5h~25h, or even 8h~20h.

[0067] In some embodiments, the temperature of the secondary sintering is 600℃~900℃, and the sintering time can be adjusted according to the actual situation, for example, it can be 5h~20h, or even 8h~15h.

[0068] In some embodiments, the pressure of the first pressing is 50 MPa to 1000 MPa, and the pressing time is 0.5 min to 30 min.

[0069] In some embodiments, the pressure of the second pressing is 50 MPa to 3000 MPa, and the time of the first pressing is 5 min to 180 min.

[0070] It should be noted that by controlling the particle size of the nickel-cobalt-manganese ternary material precursor, the primary sintering temperature and time, the type and amount of M and Me elements, the type and amount of lithium salt, the secondary sintering temperature and time, and the crushing strength after secondary sintering, it is possible to change the equivalent particle sizes β1, β2, β3 and D1, D2 of the positive electrode active material particles in the cross section to be equivalent to circles of equal area.

[0071] It should be noted that the roundness of the positive electrode active material particles on the cross-section can be altered by controlling the primary sintering temperature and time, the types and amounts of M and Me elements, and the secondary sintering temperature and time. For example, increasing Sr can increase the roundness of the positive electrode active material particles on the cross-section.

[0072] It should be noted that by controlling the composition of the nickel-cobalt-manganese ternary material precursor, the types and amounts of M and Me elements, it is possible to achieve a chemical formula of Li. a Ni b Co c M d Me e Changes in O2 compounds.

[0073] It should be noted that by controlling the type and amount of element X, the secondary sintering temperature and time, etc., it is possible to achieve a chemical formula of Li. α X β Changes in the O3 compound and the thickness of the coating layer.

[0074] In one embodiment of this application, an electrical device is provided, which includes the secondary battery described in this application.

[0075] For example, the aforementioned electrical devices may include backup power supplies, motors, electric vehicles, electric motorcycles, electric bicycles, bicycles, power tools, large household batteries, etc., but are not limited to these.

[0076] Example 1 This application provides a secondary battery, the preparation method of which includes the following steps: (1) Preparation of positive electrode active material: Ni is a ternary material precursor. 0.92 Co 0.4 Mn 0.4 (OH)2, lithium source (LiOH·H2O), Me source (ZrO2), and Me source (SrO) were mixed in a mixer at a molar ratio of 0.995:1.05:0.004:0.001, and then sintered in an oxygen-filled furnace for the first time (700℃, 12h). The material after the first sintering was then mixed with 0.5wt% Nb2O5 in a mixing device, and then sintered again in an atmosphere furnace for the second time (630℃, 8h). The material after the second sintering was then graded and sieved to select a suitable particle size, yielding 0.5wt% LiNbO3-coated Li(Ni)2O3. 0.92 Co 0.4 Mn 0.4 ) 0.995 Zr 0.004 Sr 0.001 O2 positive electrode active material; (2) Preparation of solid electrolyte layer: Solid electrolyte powder (Li6PS5Cl) is evenly spread into the mold and pre-pressed at 300MPa for 5 min in an argon glove box to form a solid electrolyte layer with a thickness of 5mm. (3) Preparation of positive electrode sheet and assembly of secondary battery: The above-mentioned positive electrode active material, solid electrolyte (Li6PS5Cl, diameter 0.6μm), binder (polyvinylidene fluoride), and conductive agent (acetylene black) were mixed in a mass ratio of 80:20:1:1, ground for 20 min and repeated 4 times to obtain a composite positive electrode material with uniform distribution of high-nickel ternary positive electrode active material and solid electrolyte. The composite positive electrode material was pressed onto the solid electrolyte layer of Li6PS5Cl under a pressure of 180 MPa to obtain a positive electrode sheet tightly bonded to the solid electrolyte layer. After placing a lithium indium alloy sheet on the other side of the solid electrolyte layer, it was pressed to obtain a secondary battery; The SEM image of the cross-section of the positive electrode sheet prepared in Example 1 is shown below. Figure 1 As shown; the equivalent particle diagram of the SEM image of the positive electrode cross-section is as follows. Figure 2 As shown.

[0077] Example 2 This application provides a secondary battery, the preparation method of which differs from that of Example 1 in that the secondary sintering coating material is 1wt% Nb2O5, ultimately yielding Li(Ni) coated with 1wt% LiNbO3. 0.92 Co 0.4 Mn 0.4 ) 0.995 Zr 0.004 Sr 0.001 O2 positive electrode active material.

[0078] Example 3 This application provides a secondary battery, the preparation method of which differs from that of Example 1 in that the secondary sintering coating material is 2wt% Nb2O5, ultimately yielding Li(Ni) coated with 2wt% LiNbO3. 0.92 Co 0.4 Mn 0.4 ) 0.995 Zr 0.004 Sr 0.001 O2 positive electrode active material.

[0079] Example 4 This application provides a secondary battery, the preparation method of which differs from that of Example 1 in that the secondary sintering coating material is 3wt% Nb2O5, ultimately yielding Li(Ni) coated with 3wt% LiNbO3. 0.92 Co 0.4 Mn 0.4 ) 0.995 Zr 0.004 Sr 0.001 O2 positive electrode active material.

[0080] Example 5 This application provides a secondary battery, the preparation method of which differs from that of Example 1 in that the secondary sintering coating material is 5wt% Nb2O5, ultimately yielding Li(Ni) coated with 5wt% LiNbO3. 0.92 Co 0.4 Mn 0.4 ) 0.995 Zr 0.004 Sr 0.001 O2 positive electrode active material.

[0081] Example 6 This application provides a secondary battery, the preparation method of which differs from that of Example 1 in that the secondary sintering coating material is 1wt% ZrO2, ultimately yielding Li(Ni) coated with 1wt% LiZrO2. 0.92 Co 0.4 Mn 0.4 ) 0.995 Zr 0.004 Sr 0.001 O2 positive electrode active material.

[0082] Example 7 This application provides a secondary battery, the preparation method of which differs from that of Example 1 in that the secondary sintering coating material is 1wt% WO3, ultimately yielding Li(Ni) coated with 1wt% Li2WO3. 0.92 Co 0.4 Mn 0.4 ) 0.995 Zr 0.004 Sr 0.001 O2 positive electrode active material.

[0083] Example 8 This application provides a secondary battery, the preparation method of which differs from that of Example 1 in that the secondary sintering coating material is 1wt% H3BO3, ultimately yielding Li(Ni) coated with 1wt% Li3BO3. 0.92 Co 0.4 Mn 0.4 ) 0.995 Zr 0.004 Sr 0.001 O2 positive electrode active material.

[0084] Example 9 This application provides a secondary battery, the preparation method of which differs from that of Example 1 in that the ternary material precursor Ni is used. 0.92 Co 0.4 Mn 0.4Li(Ni)₂ was prepared by mixing (OH)₂, lithium source (LiOH·H₂O), Me source (ZrO₂), Me source (SrO), and M source (Al₂O₃) in a molar ratio of 0.995:1.05:0.003:0.001:0.001, ultimately yielding 0.5 wt% Li₂NbO₃-coated Li(Ni)₂. 0.92 Co 0.4 Mn 0.4 ) 0.995 Zr 0.003 Sr 0.001 Al 0.001 O2 positive electrode active material.

[0085] Example 10 This application provides a secondary battery, the preparation method of which differs from that of Example 1 in that the ternary material precursor Ni is used. 0.92 Co 0.4 Mn 0.4 Li(Ni)₂ was prepared by mixing (OH)₂, lithium source (LiOH·H₂O), Me source (ZrO₂), Me source (SrO), M source (Al₂O₃), and Me source (Sb₂O₃) in a molar ratio of 0.994:1.05:0.003:0.001:0.001:0.001, ultimately yielding 0.5 wt% Li₂NbO₃-coated Li(Ni)₂. 0.92 Co 0.4 Mn 0.4 ) 0.994 Zr 0.003 Sr 0.001 Al 0.001 Sb 0.001 O2 positive electrode active material.

[0086] Example 11 This application provides a secondary battery, the preparation method of which differs from that of Example 1 in that the ternary material precursor Ni is used. 0.92 Co 0.4 Mn 0.4 Li(Ni)₂ was prepared by mixing (OH)₂, lithium source (LiOH·H₂O), Me source (ZrO₂), Me source (SrO), M source (Al₂O₃), and Me source (V₂O₅) in a molar ratio of 0.994:1.05:0.003:0.001:0.001:0.001, ultimately yielding 0.5 wt% Li₂NbO₃-coated Li(Ni)₂. 0.92 Co 0.4 Mn 0.4 ) 0.995 Zr 0.003 Sr 0.001 Al 0.001 V 0.001 O2 positive electrode active material.

[0087] Example 12 This application provides a secondary battery, the preparation method of which differs from that of Example 1 in that the ternary material precursor Ni is used. 0.92 Co 0.4 Mn 0.4 Li(Ni)₂ was prepared by mixing (OH)₂, lithium source (LiOH·H₂O), Me source (ZrO₂), Me source (SrO), M source (Al₂O₃), and Me source (Y₂O₃) in a molar ratio of 0.994:1.05:0.003:0.001:0.001:0.001, ultimately yielding 0.5 wt% Li₂NbO₃-coated Li(Ni)₂. 0.92 Co 0.4 Mn 0.4 ) 0.995 Zr 0.003 Sr 0.001 Al 0.001 Y 0.001 O2 positive electrode active material.

[0088] Example 13 This application provides a secondary battery, the preparation method of which differs from that of Example 1 in that the ternary material precursor Ni is used. 0.92 Co 0.4 Mn 0.4 Li(Ni)₂ was prepared by mixing (OH)₂, lithium source (LiOH·H₂O), Me source (ZrO₂), and Me source (SrO) in a molar ratio of 0.995:1.05:0.003:0.002, ultimately yielding 0.5 wt% Li₂NbO₃-coated Li(Ni)₂. 0.92 Co 0.4 Mn 0.4 ) 0.995 Zr 0.003 Sr 0.002 O2 positive electrode active material.

[0089] Example 14 This application provides a secondary battery, the preparation method of which differs from that of Example 1 in that the ternary material precursor Ni is used. 0.92 Co 0.4 Mn 0.4 Li(Ni)₂ was prepared by mixing (OH)₂, lithium source (LiOH·H₂O), Me source (ZrO₂), and Me source (SrO) in a molar ratio of 0.994:1.05:0.003:0.003, ultimately yielding 0.5 wt% Li₂NbO₃-coated Li(Ni)₂. 0.92 Co 0.4 Mn 0.4 ) 0.995 Zr0.003 Sr 0.003 O2 positive electrode active material.

[0090] Example 15 This application provides a secondary battery, the preparation method of which differs from that of Example 1 in that the ternary material precursor Ni is used. 0.92 Co 0.4 Mn 0.4 Li(Ni)₂ was prepared by mixing (OH)₂, lithium source (LiOH·H₂O), Me source (ZrO₂), Me source (SrO), and Me source (H₃BO₃) in a molar ratio of 0.994:1.05:0.003:0.001:0.001, ultimately yielding 0.5 wt% Li₂NbO₃-coated Li(Ni)₂. 0.92 Co 0.4 Mn 0.4 ) 0.995 Zr 0.003 Sr 0.002 B 0.001 O2 positive electrode active material.

[0091] Example 16 This application provides a secondary battery, the preparation method of which differs from that of Example 1 in that the ternary material precursor Ni is used. 0.92 Co 0.4 Mn 0.4 Li(Ni)₂ was prepared by mixing (OH)₂, lithium source (LiOH·H₂O), Me source (ZrO₂), Me source (SrO), Me source (H₃BO₃), and Me source (WO₃) in a molar ratio of 0.993:1.05:0.003:0.001:0.001:0.001, ultimately yielding 0.5 wt% Li₂NbO₃-coated Li(Ni)₂. 0.92 Co 0.4 Mn 0.4 ) 0.995 Zr 0.003 Sr 0.002 B 0.001 W 0.001 O2 positive electrode active material.

[0092] Example 17 This application provides a secondary battery, the preparation method of which differs from that of Example 1 in that Ni 0.92 Co 0.4 Mn 0.4 Li(Ni)₂, lithium source (LiOH·H₂O), me₂ source (ZrO₂), and me₂ source (SrO) were mixed in a mixer at a molar ratio of 0.995:1.10:0.004:0.001 to obtain 0.5wt% LiNbO₃-coated Li(Ni)₂.0.92 Co 0.4 Mn 0.4 ) 0.995 Zr 0.004 Sr 0.001 O2 positive electrode active material; Example 18 This application provides a secondary battery, the preparation method of which differs from that of Example 1 in that Ni 0.92 Co 0.4 Mn 0.4 Li(Ni)₂, lithium source (LiOH·H₂O), me₂ source (ZrO₂), and me₂ source (SrO) were mixed in a mixer at a molar ratio of 0.995:1.20:0.004:0.001 to obtain 0.5wt% LiNbO₃-coated Li(Ni)₂. 0.92 Co 0.4 Mn 0.4 ) 0.995 Zr 0.004 Sr 0.001 O2 positive electrode active material; Example 19 This application provides a secondary battery. The difference between the preparation method of the secondary battery and that of Example 1 is that the above-mentioned positive electrode active material, solid electrolyte (Li6PS5Cl, with a diameter of 0.6μm), binder (polyvinylidene fluoride), and conductive agent (acetylene black) are mixed in a mass ratio of 75:25:1:1.

[0093] Example 20 This application provides a secondary battery. The difference between the preparation method of the secondary battery and that of Example 1 is that the above-mentioned positive electrode active material, solid electrolyte (Li6PS5Cl, with a diameter of 0.6μm), binder (polyvinylidene fluoride), and conductive agent (acetylene black) are mixed in a mass ratio of 70:30:1:1.

[0094] Example 21 This application provides a secondary battery, the preparation method of which differs from that of Example 1 in that the diameter of the solid electrolyte in the positive electrode is 0.2 μm.

[0095] Example 22 This application provides a secondary battery, the preparation method of which differs from that of Example 1 in that the diameter of the solid electrolyte in the positive electrode is 1.5 μm.

[0096] Comparative Example 1 This application provides a secondary battery in a comparative example. The difference between the preparation method of the secondary battery and that of Example 1 is that the sintering temperature during the synthesis of the positive electrode material is increased to 850°C.

[0097] Comparative Example 2 This application provides a secondary battery in a comparative example. The difference between the preparation method of the secondary battery and that of Example 1 is that the secondary sintering temperature in the positive electrode material synthesis process is increased to 750°C.

[0098] The secondary batteries prepared in the examples and comparative examples have the following properties: β1, β2, β3; equivalent particle size D1 (equivalent to a circle of equal area on the cross-section of the positive electrode active material particles); equivalent particle size D2 (equivalent to a circle of equal area on the cross-section of the positive electrode active material particles); chemical formula of the positive electrode active material particles; chemical formula of the coating layer; mass percentage W1 of the coating layer in the positive electrode active material particles; mass percentage W2 of the solid electrolyte in the positive electrode active material layer; and diameter d of the solid electrolyte. Table 1. Parameters of Secondary Batteries Table 2 Secondary Battery Parameters Example of effect The secondary batteries prepared in the examples and comparative examples were subjected to performance tests, including the following: 1. First-cycle coulombic efficiency test: The assembled secondary battery was tested at room temperature (25℃): 1) First charge: Charge at a constant current rate of 0.1C until the voltage reaches 3.7V, then switch to constant voltage charging until the charging current drops to 0.01C and the charging is stopped. Record the cumulative charging capacity of this step as the first charge capacity Q1. 2) Let it stand: Stop charging and discharging, and let the battery stand for 10 minutes; 3) First discharge: Discharge at a constant current rate of 0.1C until the voltage drops to 2.0V, and record the cumulative discharge capacity of this step, which is denoted as the first discharge capacity Q2; 4) Let it stand: Stop charging and discharging, and let the battery stand for 10 minutes; 5) Repeat steps 1) to 4) above twice (i.e., a total of 3 cycles), and record the charge and discharge capacity in the second and third weeks; The first-round coulomb efficiency is calculated using the following formula: First-round coulomb efficiency = Q2 / Q1 × 100%; In the formula, Q1 is the initial charging capacity and Q2 is the initial discharging capacity.

[0099] 2. Double Charge Performance Test: The secondary battery after the first coulomb efficiency test cycle was tested at room temperature (25℃): 1) Charge at a constant current rate of 2C until the voltage reaches 3.7V, then switch to constant voltage charging until the charging current drops to 0.01C and the charging is stopped. Record the cumulative charging capacity of this step as the rate charging capacity Q2C. 2) Let it stand for 10 minutes; 3) Discharge at a constant current rate of 0.1C until the voltage drops to 2.0V, and record the cumulative discharge capacity of this step; 4) Calculate the rate performance (i.e., the high rate charging capacity retention rate) according to the following formula: Rate = Rate charging capacity Q2C / 0.1C first charge capacity Q1 × 100%.

[0100] The results are shown in Table 3. Table 3 Performance of Secondary Batteries As can be seen from Table 3, when the technical solution provided in this application is adopted, the obtained secondary battery has high first-cycle coulombic efficiency and rate performance. Specifically, the first-cycle coulombic efficiency of the obtained secondary battery is above 75.5%, and the rate performance is above 70.1%. As can be seen from Examples 1-22 and Comparative Examples 1-2, when the number of positive active material particles with an equivalent particle size in the range of [1.4-5) μm and a roundness in the range of [0.45-1] on a cross section perpendicular to the surface of the positive active material layer, which is equivalent to a circle of equal area, is within the range of β1 of the total number of positive active material particles on the cross section, the resulting secondary battery has excellent overall performance.

[0101] Finally, it should be noted that the above embodiments are used to illustrate the technical solutions of this application and not to limit the scope of protection of this application. Although this application has been described in detail with reference to preferred embodiments, those skilled in the art should understand that modifications or equivalent substitutions can be made to the technical solutions of this application without departing from the substance and scope of the technical solutions of this application.

Claims

1. A secondary battery, the secondary battery comprising a positive electrode sheet, the positive electrode sheet comprising a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector, the positive active material layer comprising positive active material particles. Its features are, Satisfying β1 < 8.5%, Wherein β1 represents the proportion of the number of positive electrode active material particles with an equivalent particle size in the range of [1.4~5) μm and a roundness in the range of [0.45~1] on a cross section perpendicular to the surface of the positive electrode active material layer.

2. The secondary battery according to claim 1, characterized in that, The positive electrode active material on the cross section satisfies 13% < β2 < 32%; where β2 represents the proportion of the number of positive electrode active material particles with an equivalent particle size in the range of [0.8~1.4) μm and a roundness in the range of [0.4~1) on the cross section perpendicular to the surface of the positive electrode active material layer. And / or, the positive electrode active material on the cross section satisfies 32% < β3 < 62%; where β3 represents: the proportion of the number of positive electrode active material particles with an equivalent particle size in the range of [0.2~0.8) μm and a roundness in the range of [0.3~1.5] on the cross section perpendicular to the surface of the positive electrode active material layer.

3. The secondary battery according to claim 1, characterized in that, The equivalent particle size D1 of the positive electrode active material particles on the cross section is equivalent to a circle of equal area, which satisfies 1μm≤D1≤2μm; where D1 is the particle size corresponding to the cumulative volume distribution of the positive electrode active material in the cross section of the positive electrode sheet reaching 50% based on the equivalent particle size.

4. The secondary battery according to claim 1, characterized in that, The equivalent particle size D2 of the positive electrode active material particles on the cross section is equivalent to a circle of equal area, which satisfies 2μm≤D2≤5μm; where D2 is the particle size corresponding to the cumulative volume distribution of the positive electrode active material in the cross section of the positive electrode sheet reaching 99% based on the equivalent particle size.

5. The secondary battery according to claim 1, characterized in that, The positive electrode active material particles include those with the chemical formula Li a Ni b Co c M d Me e Compounds of O2, wherein 0.95≤a≤1.05, b≥0.8, 0.05≤c≤0.15, 0.05≤d≤0.2, 0≤e≤0.05, b+c+d+e=1; M includes at least one of Mn and Al; Me includes at least one of Al, B, Zr, Zn, Sr, V, Ti, Sr, Sb, Y, W, Nb, Mg, and Ta.

6. The secondary battery according to claim 5, characterized in that, At least a portion of the surface of the positive electrode active material particles is provided with a coating layer, the coating layer comprising a chemical formula of Li α X β Compounds of O3, wherein X includes one or more of Ti, V, Cr, Zr, Nb, Si, Ta, B, La, Sr, W, and C, 0 < α < 4, 0 < β ≤ 2.

7. The secondary battery according to claim 6, characterized in that, The coating layer comprises 0.1% to 5% of the mass of the positive electrode active material particles.

8. The secondary battery according to claim 1, characterized in that, The positive electrode active material layer also includes a solid electrolyte; the diameter of the solid electrolyte is 0.2 μm to 1.5 μm.

9. The secondary battery according to claim 8, characterized in that, The mass percentage of the solid electrolyte is 1% to 50% based on the total mass of the positive electrode active material layer.

10. An electrical device, characterized in that, The electrical device includes a secondary battery as described in any one of claims 1 to 9.